“Implementación de un banco de pruebas de sistemas para el acondicionamiento de aire en el laboratorio de electromecánica de la UTC Extensión La Maná” - Giler Quiroz, Henrry Rene (2021)
The air conditioning considered to give a closed space the appropriate temperature and humidity conditions in search of the so-called comfort and air quality necessary for the well-being of people and / or the conservation of things; and at the Technical University of Cotopaxi, the Electromechanical Engineering career is a fundamental subject in the training of the future professional. Considering the importance and positive impact on the graduation profile, this chair requires the integration of theoretical and practical work, for this reason the main objective of this research is to implement a system test bench for air conditioning to be used in the laboratory of electromechanical of the UTC extension La Maná, facilitating the training given. Methodologically it is an applied, correlational research based on the utility and use of the test bench; resulting in a design for the study of air conditioning systems describing the most basic compact or window type air conditioners and the Split type so that they are manipulated by the students and identify their common components such as evaporator, condenser, compressor motor, electro fan and its particular characteristics. Concluding that with the possibility of carrying out practices to analyze and acquire applied knowledge about the operation and operation of air conditioning equipment, students will have better opportunities in the labor market and will be able to form new sources of work, in addition to acting based on good engineering practices related to air conditioning and refrigeration.